2014
DOI: 10.1371/journal.pone.0085546
|View full text |Cite
|
Sign up to set email alerts
|

Hovenia dulcis Thunb Extract and Its Ingredient Methyl Vanillate Activate Wnt/β-Catenin Pathway and Increase Bone Mass in Growing or Ovariectomized Mice

Abstract: The Wnt/β-catenin pathway is a potential target for development of anabolic agents to treat osteoporosis because of its role in osteoblast differentiation and bone formation. However, there is no clinically available anti-osteoporosis drug that targets this Wnt/β-catenin pathway. In this study, we screened a library of aqueous extracts of 350 plants and identified Hovenia dulcis Thunb (HDT) extract as a Wnt/β-catenin pathway activator. HDT extract induced osteogenic differentiation of calvarial osteoblasts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 45 publications
(50 reference statements)
1
37
0
1
Order By: Relevance
“…The results of our clinical and molecular studies indicate that topically applied MV − a safe plant‐derived ingredient – may increase both hair count and HMI by promoting WNT10B mRNA expression in the treated scalp of women with AGA. We also identified significant positive correlations between the increase of WNT10B expression in the scalp and the magnitude of increase in both hair density and HMI.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The results of our clinical and molecular studies indicate that topically applied MV − a safe plant‐derived ingredient – may increase both hair count and HMI by promoting WNT10B mRNA expression in the treated scalp of women with AGA. We also identified significant positive correlations between the increase of WNT10B expression in the scalp and the magnitude of increase in both hair density and HMI.…”
Section: Discussionmentioning
confidence: 81%
“…7 Methyl vanillate (MV) À a plant-derived ingredient that can be used in cosmetic preparationshas been previously shown to activate the WNT/b-catenin pathway in human cells in a dose-dependent manner. 18 In this report, we intended to prove the concept that stimulation of this pathway by topical MV could serve as a potential strategy for promoting hair growth in AGA. To this aim, two distinct substudies were conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Hovenia dulcis Thunb (HDT) has been traditionally applied to liver diseases in Asian countries (Hyun et al ., ). Furthermore, HDT has been scientifically proved to have anti‐fatigue (Na et al ., ), hematopoietic (Cha et al ., ), anti‐diabetes (Ji et al ., ), neuroprotective (Li et al ., ), antioxidant (Li et al ., ), hepatoprotective (Wang et al ., ), anti‐allergic (Yoshikawa et al ., ), and anti‐adipogenic (Kim et al ., ) activities to date. Nevertheless, the underlying anti‐fatty liver mechanism of HDT was not fully understood until now.…”
Section: Introductionmentioning
confidence: 99%
“…In Asian herbal medicine, H. dulcis leaves and fruits are prescribed as diuretics and antidotes (Teschke and Eickhoff 2015) and as neuro and hepatic protectors (Cha et al 2014). They are also extensively used for minimizing the effects of acute alcoholic intoxication (hangovers), since they have antioxidants capable of reducing the oxidative stress associated to alcohol metabolism (Xiong et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Therewithal, a recent study carried out by Cha et al (2014) showed that this plant synthesizes an effective anabolic agent for treating osteoporosis. However, consistent evidences indicate that the extended use of H. dulcis teas and infusions can lead to irreversible liver dysfunction, which only treatment is hepatic transplantation (Kim et al 2012).…”
Section: Introductionmentioning
confidence: 99%